Access to Credit and the Effect of Credit Constraints on the Performance of Manufacturing Firms in the East African Region: Micro Analysis - Buyinza, Faisal; Bbaale, Edward (Micro analysis, 2013)
The study set out to investigate the factors influencing manufacturing firms’ access to credit and the effect of credit constraints on firm performance in the East African Community (EAC) using the World Bank (2006) enterprise survey for 5 EAC countries. We employed simple probit, simple OLS, tobit, and a two-step probit models. Descriptively, the top five business constraints in order of severity include; electricity outages and costs, access to finance, high and volatile tax rates, corruption, and macroeconomic instability. The majority of firms within the EAC are credit constrained with only 37% of firms in the best performing sector (metal fabrications) having obtained a loan. Quantitatively, high performing firms, exporters, medium and large firms increase the probability of credit access. Findings indicate that having access to credit and a long loan duration increase firm performance, while increase in the annual interest rate reduces firm productivity. Governments in the region should tackle the business constraints rated as very severe. EAC governments should make credit access easier by lowering the annual interest rates and also negotiating for a longer pay back period for individuals in the business sector. Governments in the region should put specific attention on those sectors which are observed to have an extreme disadvantage in accessing finance.
Keywords: credit access and constraints, sales, value added, performance